2012
DOI: 10.1179/1743282011y.0000000042
|View full text |Cite
|
Sign up to set email alerts
|

New national and regional bryophyte records, 30

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 18 publications
5
49
0
Order By: Relevance
“…The moss flora of Îles Kerguelen is the richest of all subantarctic islands and until recently, it consisted of about 125 species. However, recent exploration of the archipelago yielded a number of phytogeographically and taxonomically important new records of moss (Blockeel et al, 2009a(Blockeel et al, , b, 2010Ochyra, 2010;Ellis et al, 2010Ellis et al, , 2011Ellis et al, , 2012. Thus, considering the present record and all recent additions, the moss flora of this archipelago consists of approximately 135 species and it exceeds by about 15 species that of South Georgia which has the second richest moss flora in the subantarctic region.…”
Section: Andreaea Nitida Hookf and Wilsonmentioning
confidence: 80%
“…The moss flora of Îles Kerguelen is the richest of all subantarctic islands and until recently, it consisted of about 125 species. However, recent exploration of the archipelago yielded a number of phytogeographically and taxonomically important new records of moss (Blockeel et al, 2009a(Blockeel et al, , b, 2010Ochyra, 2010;Ellis et al, 2010Ellis et al, , 2011Ellis et al, , 2012. Thus, considering the present record and all recent additions, the moss flora of this archipelago consists of approximately 135 species and it exceeds by about 15 species that of South Georgia which has the second richest moss flora in the subantarctic region.…”
Section: Andreaea Nitida Hookf and Wilsonmentioning
confidence: 80%
“…Studies by various authors (e.g. Bell, 1974;Deguchi, 1984;Bednarek-Ochyra et al, 1999;Blockeel et al, 2007Blockeel et al, , 2009aOchyra et al, 2008a,b;Ellis et al, 2011aEllis et al, ,b, 2012aEllis et al, ,b, 2013aBednarek-Ochyra & Ochyra, 1998,b,c, 2013Ochyra & van Rooy, 2013) have revealed that most of them are distinct and well defined taxa, which have nothing in common with B. crispula. As a result of critical taxonomic studies in the last two decades, no fewer than three new species of Bucklandiella were described from New Zealand (Bednarek-Ochyra & Ochyra, 1996, 2011, two reported as new (Blockeel et al, 2008;Ellis et al, 2011b) and one reinstated as a good species (Ellis et al, 2011b Campylopus pilifer is one of the commonest species of the genus in sub-Saharan Africa, ranging from Cape Verde in the Atlantic Ocean to the Mascarene Islands in the Indian Ocean (Gradstein & Sipman, 1978;Frahm, 1985a;O'Shea, 2006).…”
mentioning
confidence: 96%
“…Although knowledge of the Serbian bryophyte flora has significantly increased in the last decade, species new to the national flora continue to be recorded (e.g. Ellis et al, 2011aEllis et al, , 2012aEllis et al, ,b, 2013cPapp et al, 2012.…”
mentioning
confidence: 99%